2020
DOI: 10.32792/utq/utj/vol14/4/5
|View full text |Cite
|
Sign up to set email alerts
|

Serological and Molecular detection of Staphylococcus aureus isolated from UTI patients

Abstract: Urinary tract infections (UTIs) are one of the commonest infections encountered by clinicians despite the widespread availability of antimicrobial agents. Such Infections caused by different bacterial pathogens that can be acquired through both hospitals and the community. The present study is aimed to isolation and diagnosis of Staph. aureus , detecting the optimal antimicrobial for the treatment of these infections. A total of (600) mid-stream urine samples were collected during the period from August to Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The current study's findings showed that IL-6 was found in every serum sample, with a concentration range of 0.158-89.425 pg/ml. Also, patients with UTIs had lower mean serum levels of IL-1β (6.91 ± 11.78 pg/ml) than the control group (43.32 ± 34.62 pg/ml), as table (1) illustrates. These results were with significant differences between the patient and control groups (p≤ 0.001).…”
Section: Results and Disussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The current study's findings showed that IL-6 was found in every serum sample, with a concentration range of 0.158-89.425 pg/ml. Also, patients with UTIs had lower mean serum levels of IL-1β (6.91 ± 11.78 pg/ml) than the control group (43.32 ± 34.62 pg/ml), as table (1) illustrates. These results were with significant differences between the patient and control groups (p≤ 0.001).…”
Section: Results and Disussionmentioning
confidence: 76%
“…As shown in Table (1), pregnant women with UTIs had lower mean serum levels of IL-6 (12.08 ±16.35 pg/ml) than in the control group (42.19 ± 28.0 pg/ml). This outcome was with high significant differences (p≤ 0.002).…”
Section: Results and Disussionmentioning
confidence: 91%
See 1 more Smart Citation